2007
DOI: 10.1124/mol.107.039354
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone-Mediated Up-Regulation of HumanCYP2A6Involves the Glucocorticoid Receptor and Increased Binding of Hepatic Nuclear Factor 4α to the Proximal Promoter

Abstract: Human cytochrome P450 2A6 (CYP2A6) metabolizes various clinically relevant compounds, including nicotine-and tobaccospecific procarcinogens; however, transcriptional regulation of this gene is poorly understood. We investigated the role of the glucocorticoid receptor (GR) in transcriptional regulation of CYP2A6. Dexamethasone (DEX) increased CYP2A6 mRNA and protein levels in human hepatocytes in primary culture. This effect was attenuated by the GR receptor antagonist mifepristone (RU486; 17␤-hydroxy-11␤-[4-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 31 publications
2
43
1
Order By: Relevance
“…It did, however, decrease the frequency of nausea, vomiting, and myalgias. Because pevonedistat is a substrate of CYP3A4, we evaluated whether concurrent use of dexamethasone, a known, albeit weak, inducer of CYP3A activity via glucocorticoid receptor-mediated transcriptional upregulation (38), would increase pevonedistat systemic clearance, resulting in lower systemic exposure. On the basis of a limited sample size and after dose normalization ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It did, however, decrease the frequency of nausea, vomiting, and myalgias. Because pevonedistat is a substrate of CYP3A4, we evaluated whether concurrent use of dexamethasone, a known, albeit weak, inducer of CYP3A activity via glucocorticoid receptor-mediated transcriptional upregulation (38), would increase pevonedistat systemic clearance, resulting in lower systemic exposure. On the basis of a limited sample size and after dose normalization ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the regulators of CYP2A6 expression, we have studied transcriptional factors regulating CYP2A6 expression and found that pregnane X receptor [8] and estrogen receptor [9] are involved in the CYP2A6 regulation. In addition, a recent study reported the involvement of glucocorticoid receptor in the regulation of CYP2A6 [10].…”
Section: Introductionmentioning
confidence: 99%
“…The siRNAs of GR was previously shown to specifically abolish expression of GR (21) and RU486 was shown to inhibit the function of 15-LOX-2 (22,23). The luciferase assays showed that the treatment with siRNAs of GR was able to reverse the inhibitory effect of GR on promoter activities of LF4 and LF7, GR reduced luciferase activities of LF4 and LF7 to 60.73%±2.09 and 56.11±2.94, respectively, but these were up to 86.17±3.60 and 138.57±3.03, respectively after the treatment with siRNAs of GR.…”
Section: The Inhibitory Effect On 15-lox-2 Promoter Activity By Gr Wamentioning
confidence: 99%